Arte e décadence em Nietzsche: o caso Wagner e outros escritos - Petry, Isadora Raquel (2015)
This dissertation aims at presenting some aspects of Nietzsche's theory of décadence. It limits itself to Nietzsche's confrontation with 19th century art and focuses on the way in which Nietzsche undertakes, by means of the décadent-artists, a certain diagnosis and a certain critique of his own epoch, i.e, of modernity. In order to bring this diagnosis to light the philosopher undertakes an analysis of certain artists; among these it is Richard Wagner the one who best expresses the modern condition. In The case of Wagner, written in 1888, Nietzsche interprets the musician as a very great actor owing to Wagner's necessity to disguise, to travesty a decadent and fragmented reality into a seemingly unified and coherent form. Art is thus transformed into an art of seduction and excitement, into an attempt at escaping from reality. But if décadent art is, according to Nietzsche, the means by which to detect the dangers of the present, it is also, on the other hand, only through it that the philosopher envisages an overcoming of modernity itself and of the décadence which constitutes it. In order to introduce ourselves to the genealogic-physiologic procedures by which Nietzsche analyses décadent art, we have shown (Chapter 1) some aspects of the first form of decadence diagnosed by Nietzsche, the socratic decadence of hellenic culture such as made explicit in The Birth of Tragedy (1872). Thereupon we brought to light (Chapter 2) some elements of the historical context out of which the concept décadence emerged in the French literary milieu, thus approaching the theme of Nietzsche's reception particularly of the literary critic Paul Bourget and of the poet Charles Baudelaire. Furthermore we analysed (Chapter 3) some aspects of the décadent art departing from the nietzschean diagnosis of Wagner's Gesamtkunstwerk , setting as background thereto the problem of the actor and the critique of theatrocracie developed in Nietzsche's later philosophy. We concluded our dissertation by indicating how Nietzsche envisages the possibility of an immanent overcoming of décadence